Kelayakan Raspberry Pi sebagai Web Server: Perbandingan Kinerja Nginx, Apache, dan Lighttpd pada Platform Raspberry Pi - Rahmad Dawood; Said Fairuz Qiana; Sayed Muchallil (Universitas Syiah Kuala, 2014)
Raspberry Pi is a small-sized computer, but it can function like an ordinary computer. Because it can function like a regular PC then it is also possible to run a web server application on the Raspberry Pi. This paper will report results from testing the feasibility and performance of running a web server on the Raspberry Pi. The test was conducted on the current top three most popular web servers, which are: Apache, Nginx, and Lighttpd. The parameters used to evaluate the feasibility and performance of these web servers were: maximum request and reply time. The results from the test showed that it is feasible to run all three web servers on the Raspberry Pi but Nginx gave the best performance followed by Lighttpd and Apache.Keywords: Raspberry Pi, web server, Apache, Lighttpd, Nginx, web server performance